Analisis Survival Lama Masa Pengobatan Dan Tingkat Kesembuhan Pasien Narkoba Di Lembaga Terapi Dan Rehabilitasi Pondok Pesantren Ibadurrahman Tenggarong Seberang - Fathur Rachman; Sri Wahyuningsih; Yuki Novia Nasution (Program Studi Statistika FMIPA Universitas Mulawarman, 2016)
Survival analysis is used to analyze of the long life data, in general this method used to estimate and the time curve survival which is Life Table Method, Model of Cox Proportional Hazard or the Cox model and Product Limit Method (Kaplan Meier). This script well knowing about the model of Cox Proportional Hazard for the influencing factors in the recovery term of the Narcotics Patients in the Institution of Therapy and Rehabilitation Pondok Pesantren Ibadurrahman Tenggarong Seberang and knowing of the influencing factors in the recovery term of the Narcotics Patients in the Institution of Therapy and Rehabilitation Pondok Pesantren Ibadurrahman Tenggarong Seberang. The research data is done for 114 of Narcotics Patients. The Procedural in making Cox Proportional Hazard model including to several parts, they are deciding of variables which used to, assumption exam of Cox Proportional Hazard model, choosing the best model with backward exam, deciding variable which influenced of the cure rates duration. The usage data are forming by 5 variables, such as Gender, Education, The use of Smoking, Ages, and Parenting, based on the research was found the model of Cox Proportional Hazard for the influence factors in hi curing is: hi(t,x)=exp(-0.694 x4) h0(t). The influence factors in curing of the Narcotics Patients are the age of the patient since the therapy.